ANALISIS PENGARUH KUALITAS LAYANAN, TARIF, LOKASI, FASILITAS, TERHADAP LOYALITAS PELANGGAN (studi empiris pada Hotel Masjid Agung Jawa Tengah Semarang) - Aditya Nur Haryanto, 08.05.51.0004; Suko Priyono, Bambang (Students Journal of Economic and Management, 2012)
The study entitled "Analysis of Effect of Quality of Service, Hotel Rates, Location, and Amenities for Customer Loyalty (Studies in the Great Mosque of Semarang House Hotel on Jl. Elephant Kingdom, Semarang)". This study analyzes the effect of quality of service (X1), the room rate (X2), the location of the hotel (X3), facilities services (X4) on customer loyalty (Y). The population in this study is the hotel customers are enjoying the Wisma Great Mosque of service, price, location and facilities diberiikan by the hotel. Determination of the samples was done by using "accidential sampling" and the number of samples taken as many as 110 people. Analytical model used is multiple linear regression. Previously, the validity and reliability testing. The research results are: (1) The results of statistical calculations with multiple linear regression analysis can be shown by the regression equation Y = 0.474 + -0.097 X1 -0.005 X2 + X3 + X4 + 0.455 e. From the regression equation is known that the quality of services and facilities have a positive and significant influence on customer loyalty, while at the rates and location has no significant influence on customer loyalty. (2) The calculation of the coefficient of determination 0.688 magnitude. This suggests that the quality of service, rates, location, facilities are able to explain the variable customer loyalty by 68.8%. While the remaining 31.2% is explained by other variables not examined such as customer satisfaction, product quality, and others. (3) The hypothesisthat has been done in this study were: A) There is a significant and positive influence of service quality on customer loyalty. B) no significant effect on customer loyalty rates. C) There was no significant effect on customer loyalty sites. D) There is a significant and positive influence on customer loyalty sites.Keywords: Quality of service, rates, location, facilities and customer loyalty.